Entrepreneurial Intent of Filipino Undergraduate Health Sciences Stu-dents: A Descriptive Cross-Sectional Study - Angeles, Raul G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This quantitative study, grounded in Ajzen’s (1991) Theory of Planned Behavior (TPB), investigates the entrepreneurial inten-tions of Filipino undergraduate health sciences students using a descriptive cross-sectional research design. The study involved 820 respondents from various health sciences programs in North Luzon, Philippines, who completed an online survey. Demographic characteristics and entrepreneurial intent were assessed through a researcher-designed Demographic Profile Questionnaire (DPQ) and the Individual Entrepreneurial Intent Scale (IEIS) established by Thompson (2009). This study adopts a positivist view, empha-sizing objectivity, consistency, and replicability through statistical methods. The findings reveal that the undergraduate health sci-ences students demonstrate a “good” level of entrepreneurial in-tentions, with a notable significant variation observed between those who have taken business-related courses and those who have not, with the former exhibiting higher intent. Other factors, such as age, gender, and marital status, did not show significant differences in entrepreneurial intentions, suggesting that educa-tional experiences play a more critical role than personal charac-teristics. The study recommends educational strategies and poli-cies, such as curricular enhancement towards entrepreneurial ed-ucation in health sciences education, to foster innovation and en-courage healthcare entrepreneurship. Overall, this research con-tributes to the expanding literature on entrepreneurship; however, like other studies, it has limitations. Therefore, future research directions are offered.